Cohort 1 - Call for Applications Report - Ng'anga, Salome; Zulu-Hume, Mercy F. (2023)
The Call for Applications resulted in a total of 849 applicants, out of which 288 met the high-quality standards for prequalification. The accelerator program successfully attracted women-led or co-led agribusinesses, with 69% of applicants featuring at least one woman in the founding team. The majority of applicants (72%) indicated that they were targeting smallholder farmers in their business model, and 52% claimed to have a digital innovation, highlighting the potential for technology in transforming the food systems sector. The most mentioned crops were maize, beans, soya beans, potatoes, livestock, and rice, underscoring the importance of diversifying food production. The accelerator program core team analyzed the performance of the Call for Applications and recommended several strategies to improve the next Call. Based on the insights gained, the team suggested reducing the number of required attachments to increase the completion rate of applications. The team also plans to target previous applicants who almost made it to the shortlist with personalized emails to encourage them to reapply. In addition, the team recommended exploring alternative marketing strategies to reach potential applicants who are not active on social media, and partnering with local accelerators and incubators to leverage their networks and resources.